Hubungan Aktivitas Fisik dan Tingkat Stress Dengan Kualitas Tidur Mahasiswa Tingkat Akhir Program Studi S1 Keperawatan - Maziyyah, Alya Nurul; Suryati, Tati (STIKES Ngesti Waluyo, 2023)
Sleep quality is a state of sleep experienced by an individual resulting in freshness and well-being when awakened. Risk factors such as high physical activity and high levels of stress can result in poor sleep quality. This study aims to determine the relationship between physical activity and stress levels with the quality of sleep for final year students of the Undergraduate Nursing study program batch XII at STIKes Pertamedika. This research design used descriptive analytic with cross sectional approach. The population in this study were 65 students. This sampling technique used the Total Sampling technique. The research instrument used a questionnaire. The results of the study based on the Chi Square statistical test showed that there was a relationship between physical activity and sleep quality (p-value=0.001), and there was a relationship between stress levels and sleep quality (p-value=0.001). Based on this research, it is hoped that it can be used as material for education and additional sources of information about the importance of managing time for physical activity and stress levels in order to get good sleep quality.